2019
DOI: 10.3126/jpn.v9i1.23173
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic role of bronchoalveolar lavage: A cytohistopathological correlation

Abstract: Background: Tumors of lung are common in Nepal. The risk of malignancy has to be judged prior to surgery for which bronchoscopy is often done. Brocho-alveolar lavage and bronchial biopsy are routine procedure done for diagnosis of lung cancer during bronchoscopy. This study was done to correlate the cytology of broncho-alveolar lavage specimen with histopathology in malignant tumors of the lug in our setup. Materials and methods: This study was conducted at department of pathology, Nobel Medical College … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…19 But contradictory results were also observed in some studies, like a study by Choudhury et al where they found the sensitivity, specificity, positive predictive value, negative predictive value, and overall accuracy of BAL at 88.1%, 97.98%, 94.7%, 95.1%, and 95.03% respectively. 20 The sensitivity was more prominent in these discrepancies. This might be related to the number of attempts at obtaining BAL sampling.…”
Section: Discussionmentioning
confidence: 97%
“…19 But contradictory results were also observed in some studies, like a study by Choudhury et al where they found the sensitivity, specificity, positive predictive value, negative predictive value, and overall accuracy of BAL at 88.1%, 97.98%, 94.7%, 95.1%, and 95.03% respectively. 20 The sensitivity was more prominent in these discrepancies. This might be related to the number of attempts at obtaining BAL sampling.…”
Section: Discussionmentioning
confidence: 97%